Some Features of the Coverage of Crimes during the War in the Context of the Karabakh Conflict - Hambardzumyan, Naira (Bulletin of Yerevan University B: Philology, 2022)
For professional and targeted reporting of war crimes of the parties during wars, armed conflicts, crimes againsthumanity, etc., not only professional knowledge and skills in the field of journalism butalso certain levels of professional training are required, including a high level of awareness of the historical background of the conflict, political events, the activities of theinternational organizations, the sphere of jurisdiction, knowledge of various branches ofinternational law, knowledge of the possibilities of journalistic work in the internationalcourts, accreditation procedures, work style, forms, etc.The mentioned above knowledge can help in terms of comparison of facts, initiateinvestigations, identify issues, inform the public about what is observable to all, and, themost important, this basis can become a guide in shaping new views and perceptions ofthe conflict and its geopolitical processes. The article deals with the research topic in thecontext of the Karabakh conflict, in particular, the 44-day war.
Keywords: Karabakh conflict; war crimes; human rights; international criminal law; coverage of armed conflicts; military journalism